Comparison of the Associations of Early-Life Factors on Wheezing Phenotypes in Preterm-Born Children and Term-Born Children. Issue 3 (22nd January 2019) - Kotecha, Sarah J; Watkins, W John; Lowe, John; Granell, Raquel; Henderson, A John; Kotecha, Sailesh
Abstract: Although respiratory symptoms, including wheezing, are common in preterm-born subjects, the natural history of the wheezing phenotypes and the influence of early-life factors and characteristics on phenotypes are unclear. Participants from the Millennium Cohort Study who were born between 2000 and 2002 were studied at 9 months and at 3, 5, 7, and 11 years. We used data-driven methods to define wheezing phenotypes in preterm-born children and investigated whether the association of early-life factors and characteristics with wheezing phenotypes was similar between preterm- and term-born children. A total of 1, 049/1, 502 (70%) preterm-born children and 12, 307/17, 063 (72%) term-born children had recent wheeze data for 3 or 4 time points. Recent wheeze was more common at all time points in the preterm-born group than in term-born group. Four wheezing phenotypes were defined for both groups: no/infrequent, early, persistent, and late. Early-life factors and characteristics, especially antenatal maternal smoking, atopy, and male sex, were associated with increased rates for all phenotypes in both groups, and breastfeeding was protective in both groups, except late wheeze in the preterm group. Preterm-born children had similar phenotypes to term-born children. Although early-life factors and characteristics were similarly associated with the wheezing phenotypes in both groups, the preterm-born group had higher rates of early and persistent wheeze. However, a large proportion of preterm-born children had early wheeze that resolved with time.